Development of an Acupressure Animation Video to Enhance the Facial Care Competency of Vocational High School Students - Alia Rakhmawati; Ali Muhtadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective instructional media are crucial in vocational education, particularly in enhancing students’ practical skills. This study aims to develop an animation video for acupressure learning, assess its eligibility and practicality, and evaluate its effectiveness in improving student competency. A Research and Development (RD) approach was employed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted at SMK Negeri 1 Kota Batu, East Java, during the 2023/2024 academic year. Participants included 10 students for needs analysis, 2 expert validators for content and product evaluation, 20 students for the experimental phase, and 2 teachers for practicality assessment. Data collection involved questionnaires, expert judgments, and pre-test/post-test measures, analyzed through qualitative and quantitative techniques. The animation video was successfully developed following all ADDIE stages. Expert validation indicated high content eligibility, with an average feasibility score of 93.75%. Practicality evaluations by two Facial Care teachers confirmed that the product is suitable for acupressure learning. Furthermore, inferential analysis comparing the control and experimental groups revealed a significant improvement in students' acupressure competency after using the animation video. The results suggest that the developed animation video is both practical and effective in enhancing acupressure learning outcomes. Its high validity and positive reception highlight its potential applicability across other vocational schools to support facial care instruction. The animation video demonstrates strong potential as an instructional tool for improving students' competency in acupressure within vocational education settings.